2016
DOI: 10.1177/0956797616654911
|View full text |Cite
|
Sign up to set email alerts
|

The Bitter Truth About Sugar and Willpower

Abstract: According to the law of conservation of energy, the total amount of energy of an isolated system can never increase. In the domain of psychology, the idea that energy is a limited resource originated with Freud (1923Freud ( /1961. Energy models have been little used in psychology since Freud, though, with the rare exception of the ego-depletion model developed by Baumeister, Bratslavsky, Muraven, and Tice (1998). According to this research, "the self's acts of volition draw on some limited resource, akin to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(30 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“… 1 If the glucose-as-self-control-resources hypothesis (Gailliot et al, 2007) had received strong support, this would have resolved the circular-logic problem, but, given the growing evidence against this hypothesis (Beedie and Lane, 2012; Dang, 2016; Vadillo et al, 2016), the field still lacks independent, noncircular evidence for the domain-generality assumption.…”
mentioning
confidence: 99%
“… 1 If the glucose-as-self-control-resources hypothesis (Gailliot et al, 2007) had received strong support, this would have resolved the circular-logic problem, but, given the growing evidence against this hypothesis (Beedie and Lane, 2012; Dang, 2016; Vadillo et al, 2016), the field still lacks independent, noncircular evidence for the domain-generality assumption.…”
mentioning
confidence: 99%
“…The lack of impact from soft drinks and food on LOC is consistent with a recent meta study on the relationship between glucose and self-control. It demonstrated that the evidence on such a relationship is weak (Vadillo et al 2016).…”
Section: Consumption's Impact On Cognitive and Non-cognitive Scoresmentioning
confidence: 99%
“…The subjective value function for the single evaluation (SE) mode is presented as the solid line, whereas the function for the joint evaluation (JE) mode is presented as the dashed line. General evaluability theory proposes that subjective value functions are more linear in JE across values than in SE (adapted from Hsee & Zhang, 2010) Hockey, 2011 ;Inzlicht & Schmeichel, 2013Job, Walton, Bernecker, & Dweck, 2013;Kelly, Sünram-Lea, & Crawford, 2015;Lange & Eggert, 2014;Lurquin et al, 2016;Kurzban, 2010;Kurzban, Duckworth, Kable, & Myers, 2013;Raichle & Mintun, 2006;Vadillo, Gold, & Osman, 2016;Westbrook & Braver, 2015). Furthermore, whether or not similar systems underlie evaluation of both physical and cognitive effort remains to be determined (Westbrook & Braver, 2015;cf.…”
Section: The Evaluability Of Effortmentioning
confidence: 99%